Deteksi Mycobacterium Avium Subspesies Paratuberculosis pada Susu Pasturisasi yang Dijual di Bogor - Sri Nugroho, Widagdo; Sudarwanto, Mirnawati; Widaya Lukman, Denny; Setyaningsih, Surachmi; Usleber, Ewald (Jurnal Veteriner; Vol 11 No 2 (2010), 2010)
Mycobacterium avium subspesies paratuberculosis (MAP) is a thermal tolerant bacteria. The presenceof these bacteria in pasteurized dairy milk is associated with infectious bowel disease in human known asCrohn’s disease. The aim of this study was to detect MAP in pasteurized dairy milk sold in Bogor. Fourtytwo samples of plain flavoured milk (180–250 ml) from 7 producers were bought from supermarkets inBogor. The presence of MAP was detected by isolation and conventional polymerase chain reaction (PCR)using IS 900 and F57. Bacterial isolation were done by Herrold’s egg yolk medium with mycobactine J(HEYMj) and without mycobactin J (HEYM) and incubated at 37°C for 20 weeks. The DNA extraction ofall pasteurized dairy milk samples were conducted by DNeasy® Tissue Kit. Amplification conditionsfor PCR were: 1 cycle at 94°C for 10 minutes, 40 cycles at 94°C for 1 minute, 58°C for 1 minute, and72°C for 3 minutes, and 1 cycle at 72°C for 7 minutes. After 20 weeks of incubation, there were no sign ofMAP which grew in all isolation mediums. The PCR IS 900 and F57 did not detect the DNA band of thetarget. In the conclusion, there was no MAP detected in pasteurized dairy milk sold in Bogor.
Keywords: Mycobacterium avium subspesies paratuberculosis, pasteurized, dairy milk